Pengaruh Penggunaan Aplikasi VUE Terhadap Hasil Belajar PPKn Di MIN 4 Aceh Tamiang - Zulika, Nora (Mulya Literasi Publishing, 2022)
Learning media is a means to make it easier for students to understand the material provided so student learning outcomes can improve. Therefore, learning media is needed that can help students in the learning process, one of which is the development of learning media in the form of audio-visual, namely the use of video editing applications, namely VUE. The purpose of this study was to determine the effect of using the VUE application on PPKN learning outcomes in MIN 4 Aceh Tamiang for the 2021/2022 Academic Year. The research design used in this study used an experimental method with the type of Quasi Experiment (Pseudo-Experiment). The results of this study are known that the average score of PPKN learning outcomes in class V MIN 4 Aceh Tamiang has increased. Thus, it can be concluded that the use of the VUE application affects the learning outcomes of PPKN in class V at MIN 4 Aceh Tamiang. This can be seen from the learning outcomes of students in PPKN subjects in experimental classes that are higher than control classes.